Idiopathic granulomatous mastitis with erythema nodosum and polyarthritis - J. Alungal; M.C. Abdulla; R. Narayan (Reumatismo, 2016)
A 25 year-old woman presented with a painful mass in the left breast, polyarthritis and erythema nodosum. Fine needle aspiration cytology led to a diagnosis of granulomatous mastitis. Oral prednisolone rapidly improved the arthritis and the erythema nodosum. Granulomatous mastitis is a very rare, chronic inflammatory disease and only ten patients with granulomatous mastitis with erythema nodosum and polyarthitis have been described.